Lean TPM : a blueprint for change - McCarthy, Dennis (Elsevier Butterworth-Heinemann, 2004)
Merging the benefits of two well-known methodologies, Lean Thinking and Total Productive Maintenance, Lean TPM shows how to secure increased manufacturing efficiency. Based on their experienc of working with organisations that have successfully achieved outstanding performance, McCarthy and Rich provide the tools and techniques that convert strategic vision into practical reality. Lean TPM accelerates the benefits of continuous improvement activities within any manufacturing environment by challenging wasteful working practices, releasing the potential of the workforce, targeting effectiveness.